Prevalence and molecular identification of hypodermosis from slaughtered cattle in Sulaymaniyah province, Iraq - Aram A Mohammed; Taib A Hama Soor; Mardin O Abdulqadir (Journal of Infection in Developing Countries)
Introduction: Hypodermosis is a subcutaneous infestation in cattle that is caused by larvae of Hypoderma spp. and it is an economically important disease in the cattle industry. This study aimed to find the prevalence rate of hypodermosis and identify variations in the COX1 gene among isolates present in Sulaymaniyah, in the Kurdistan region of Iraq.